2020
DOI: 10.1080/10410236.2020.1838096
|View full text |Cite
|
Sign up to set email alerts
|

Considering Emotion in COVID-19 Vaccine Communication: Addressing Vaccine Hesitancy and Fostering Vaccine Confidence

Abstract: Long-term control of the COVID-19 pandemic hinges in part on the development and uptake of a preventive vaccine. In addition to a segment of population that refuses vaccines, the novelty of the disease and concerns over safety and efficacy of the vaccine have a sizable proportion of the U.S. indicating reluctance to getting vaccinated against COVID-19. Among various efforts to address vaccine hesitancy and foster vaccine confidence, evidence-based communication strategies are critical. There are opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
502
6
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(531 citation statements)
references
References 40 publications
10
502
6
13
Order By: Relevance
“…A study in China found that 48% of respondents postponed vaccination before confirmation of the safety of the vaccine [34], which shows their doubt regarding vaccine safety. Worryingly, the exceptionally rapid pace of vaccine development, the skepticism of certain groups of science and health experts might elevate doubt about COVID-19 vaccine [38]. According to our study, 95% participants reported that the vaccine should be free for people in Bangladesh, which is inconsistent with a previous study in Indonesia, where most of the respondents were willing to pay for the COVID-19 vaccine [39].…”
Section: Discussioncontrasting
confidence: 98%
“…A study in China found that 48% of respondents postponed vaccination before confirmation of the safety of the vaccine [34], which shows their doubt regarding vaccine safety. Worryingly, the exceptionally rapid pace of vaccine development, the skepticism of certain groups of science and health experts might elevate doubt about COVID-19 vaccine [38]. According to our study, 95% participants reported that the vaccine should be free for people in Bangladesh, which is inconsistent with a previous study in Indonesia, where most of the respondents were willing to pay for the COVID-19 vaccine [39].…”
Section: Discussioncontrasting
confidence: 98%
“…They may also reflect the inherent role that emotions, personal values, and worldviews play in health decision making, 30-32 a key facet for public health communicators to take into account when marketing novel vaccines to both the healthcare community and the general public. 33…”
Section: Discussionmentioning
confidence: 99%
“…According to Fishbein and Ajzen [62], effective communication should stress which behaviors have to be changed, further providing the public with clear instruction as to how this change can be obtained [3]. Therefore, message should appeal to individuals' self-efficacy [63,64]. Self-efficacy is activated if identification with message content is high [43,44].…”
Section: Appeal To Individuals' Self-efficacymentioning
confidence: 99%